Inconsistency in the Implementation of Corruption Criminalization Guidelines Based on PERMA No. 1 of 2020 in the Harvey Moeis Case Decision - Cristofel, Moses; Prasetyo, Boedi (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
This study analyzes the inconsistency in applying Supreme Court Regulation (PERMA) No. 1 of 2020 on Sentencing Guidelines for Corruption Cases in the Central Jakarta District Court Decision No. 70/Pid.Sus-TPK/2024/PN.Jkt.Pst concerning Harvey Moeis. The research employs a normative juridical method with statutory and conceptual approaches, using library research on primary, secondary, and tertiary legal materials analyzed through a descriptive qualitative framework. The findings reveal that the sentencing failed to align with the principles of proportionality and justice mandated by PERMA No. 1 of 2020. Weak judicial oversight, subjective interpretation by judges, and declining professional ethics have led to sentencing disparities that erode public trust in judicial integrity. Systemic reconstruction is therefore required through stronger compliance mechanisms, an enhanced role of the Judicial Commission, and moral-based judicial training to ensure the consistent realization of substantive justice.